Possibilities of long-term effective treatment of idiopathic pulmonary arterial hypertension by replacing sildenafil with riociguat and using sequential combination therapy: case report - S. A. Musashaykhova; Z. S. Valieva; A. K. Osokina; I. Z. Korobkova; V. V. Gramovich; N. M. Danilov; T. V. Martynyuk (Евразийский Кардиологический Журнал, 2022)
Modern pathogenetic therapy of idiopathic pulmonary arterial hypertension (IPAH), a severe life-threatening cardiovascular disease of unknown etiology, leads to a positive clinical effect due to reverse remodeling of the vessels of the microvasculature of the lungs. Highly effective drugs of specific therapy that act on the main targets of pathogenesis have now been introduced into clinical practice.The presented clinical case of a patient with diagnosed in 2014 IPAH with an initial functional class III according to the WHO classification demonstrates high long-term efficacy and safety of specific therapy based on the use of the soluble guanylate cyclase stimulator riociguat for 5 years after replacing previous therapy with sildenafil with further implementation of the strategy of sequential combination therapy due to the addition of ambrisentan and selexipag.